Securitization: Terrorism prevention policy in Poso Regency, Central Sulawesi - Gustiana Kambo (Masyarakat, Kebudayaan dan Politik, 2022)
The existence of terrorism in Poso Regency, Central Sulawesi is triggered by a communal conflict among religions since 2000. A series of acts of terrorism have disrupted the regulation of government and public order and security, so that the regional government carried out special handling of this case. The objective of this study is to analyze the pattern of terrorism prevention carried out by the regional government in Poso Regency. This study used a qualitative method with a case study approach to conduct an in-depth descriptive study regarding the pattern of strengthening the terrorism prevention policy and its follow-up. In analyzing this case, this study used the concept of securitization developed by Buzan (1991) through the principles of social, economic, and political security. The results of the study showed that the regional government has made efforts to prevent acts of terrorism by (1) Strengthening the Early Detection of Terrorism Tendency Program, (2) Strengthening the Religious Harmony Program, (3) Strengthening the Community Social Life Program, (4) Strengthening the Entrepreneurship Program that covers various activities, including; establishing Village of Harmony and Early Awareness Forum, carrying out counseling on Pancasila values, providing social assistance and entrepreneurship training for the poor and families of ex-terrorism convicts. This study concludes that the regional government has made systematic efforts with a securitization approach in a strict security pattern with community involvement.